Profil Perkembangan Anak Autism Spectrum Disorder dan Implikasinya terhadap Layanan Konseling : - Muh Rijal; Rosita Hidija (CV. ITTC INDONESIA, 2026)
Children with autism have diverse developmental characteristics in various aspects, requiring educational and counseling services tailored to their individual needs. This study aims to describe the developmental profile of children with autism and analyze its implications for counseling services in schools. The study uses a qualitative approach with a descriptive-analytical method. The research subjects consisted of two children who had been diagnosed with autism. Data collection was conducted through developmental assessments using checklist instruments and structured observations on gross motor skills, fine motor skills, verbal language, nonverbal language, and attention. The data were analyzed descriptively, quantitatively, and qualitatively. The results showed that gross motor skills, nonverbal language, and attention were in the instructional level category. Fine motor skills showed differences between subjects, namely in the independent level and frustration level categories. Meanwhile, verbal language skills in both subjects were in the independent level category, although still functional. These findings indicate that the developmental profile of children with autism varies between aspects and individuals. Therefore, developmental assessment needs to be used as a basis for designing counseling services that are individualized, adaptive, and appropriate to the developmental needs of children in the school environment.